Study on Palm Vein Authentication - Sasidharan, Sibi; Azath, M Azath (International Journal of Computer Sciences and Engineering, 2015)
Biometrics is a method by which a person's authentication information is generated by digitizing measurements of a physiological or behavioral characteristic. Biometric authentication checks user's claimed identity by comparing an encoded value with a stored value of the concerned biometric characteristic. Various biometric authentications are face recognition, fingerprints, hand geometry etc .Among this, the most recent technology is palm vein authentication. Various techniques have been proposed by researchers in the area of palm vein identification. Most of the methods uses various features of palm vein like geometric, cosine similarity, wavelet features etc but lags with the accuracy of identification and authentication. Authentication using hand geometry does not have the same degree of permanence or individuality as other characteristics. Even authentication using Cosine similarity and wavelet features lags in accuracy. Palm vein authentication is highly accurate and secure since the authentication data exists inside the body and it is difficult to forge. It uses vascular patterns as personal identification data. This paper presents the analysis of various methods and algorithms that identifies the vein patterns in palm for authentication purpose.